Don’t Do-It-Yourself: The Exquisite Corpse and Collaborative Play in Undergraduate Electronic Music Pedagogy - Josh Biggs (Journal of the Association for Technology in Music Instruction, 2026)
In this demonstration, I focus on the Exquisite Corpse as a pedagogical tool for undergraduate electronic music production courses, and more broadly argue for the practical and theoretical value of integrating collaborative and iterative improvisational tools in undergraduate electronic music curricula. I share a four-week module that applies the Exquisite Corpse method as a way to reduce student overwhelm and to encourage community-oriented learning and making, while introducing simple subtractive synthesis and MIDI composition in the DAW. The audience will benefit both from the specificity of the teaching methods I outline as well as the motivating premise that electronic music pedagogy both rewards and is rewarded by an emphasis on open, procedural, and cooperative creativity.